Tissue remodelling and increased DNA damage in patients with incompetent valves in chronic venous insufficiency. Issue 16 (20th June 2021) - Ortega, Miguel A.; Fraile‐Martínez, Oscar; García‐Montero, Cielo; Pekarek, Leonel; Alvarez‐Mon, Miguel A.; Guijarro, Luis G.; del Carmen Boyano, Maria; Sainz, Felipe; Álvarez‐Mon, Melchor; Buján, Julia; García‐Honduvilla, Natalio; Asúnsolo, Ángel
Abstract: Chronic venous insufficiency (CVI), in which blood return to the heart is impaired, is a prevalent condition worldwide. Valve incompetence is a complication of CVI that results in blood reflux, thereby aggravating venous hypertension. While CVI has a complex course and is known to produce alterations in the vein wall, the underlying pathological mechanisms remain unclear. This study examined the presence of DNA damage, pro‐inflammatory cytokines and extracellular matrix remodelling in CVI‐related valve incompetence. One hundred and ten patients with CVI were reviewed and divided into four groups according to age (<50 and ≥50 years) and a clinical diagnosis of venous reflux indicating venous system valve incompetence (R) (n = 81) or no reflux (NR) (n = 29). In vein specimens (greater saphenous vein) from each group, PARP, IL‐17, COL‐I, COL‐III, MMP‐2 and TIMP‐2 expression levels were determined by RT‐qPCR and immunohistochemistry. The younger patients with valve incompetence showed significantly higher PARP, IL‐17, COL‐I, COL‐III, MMP‐2 and reduced TIMP‐2 expression levels and a higher COL‐I/III ratio. Young CVI patients with venous reflux suffer chronic DNA damage, with consequences at both the local tissue and systemic levels, possibly associated with ageing.